Exploring the Meaning of the Secret Book of Bainal Haq as a Literature Learning: A Study of Ludwig Wittgenstein's Philosophy of Language - Chaer, Hasanuddin; Rasyad, Abdul; R., Januari Rizki Pratama; Setiawan, Irma; Hidayat, Rahmad; Ramdhani, Marlinda (Muslim Education Review, 2025)
This article delineates the stylistic similarities between Hölderlin's poetry and Sufi poetry within the manuscript of the 'Secret Book of Bainal Haq'. Accordingly, this research aims to highlight the shared stylistic features found in both types of poetry within the context of understanding the existence of God. The expressions of Sufi poetry contained therein reflect universal spiritual symbols capable of transcending cultural and historical boundaries. The Sufi literary discourse in the 'Secret Book of Bainal Haq' is connected to past literary traditions and anticipates the future direction of literature, as reflected in the poetry and metaphors used in the manuscript. This research approach adopts a qualitative descriptive content analysis method, employing Wittgenstein's 'Philosophical Investigations' approach. The research findings demonstrate that this approach effectively traces the relationship between transcendental existence (God) and religious aspects through Sufi literature in the 'Secret Book of Bainal Haq'. Within the framework of this research, the philosophy of language is considered an effective tool for understanding transcendental existence through literary discourse.